2015
DOI: 10.1021/acs.est.5b03109
|View full text |Cite
|
Sign up to set email alerts
|

Contaminants of Emerging Concern: Mass Balance and Comparison of Wastewater Effluent and Upstream Sources in a Mixed-Use Watershed

Abstract: Understanding the sources, transport, and spatiotemporal variability of contaminants of emerging concern (CECs) is important for understanding risks and developing monitoring and mitigation strategies. This study used mass balances to compare wastewater treatment plant (WWTP) and upstream sources of 16 CECs to a mixed-use watershed in Minnesota, under different seasonal and hydrological conditions. Three distinct CEC groups emerged with respect to their source proportionality and instream behavior. Agricultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
57
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 55 publications
7
57
1
Order By: Relevance
“…Pharmaceutical input, removal efficiencies, and seasonal variation of PPCPs in conventional wastewater treatment systems is increasingly well documented (such as Yu et al (2013); Fairbairn et al (2016); Papageorgiou et al (2016). However, information on seasonal PPCP occurrence in forest water reuse systems (open-air reservoirs, soils, groundwater, and surface waters) is limited but needed to evaluate the water regulating services provided by these green infrastructure systems.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmaceutical input, removal efficiencies, and seasonal variation of PPCPs in conventional wastewater treatment systems is increasingly well documented (such as Yu et al (2013); Fairbairn et al (2016); Papageorgiou et al (2016). However, information on seasonal PPCP occurrence in forest water reuse systems (open-air reservoirs, soils, groundwater, and surface waters) is limited but needed to evaluate the water regulating services provided by these green infrastructure systems.…”
Section: Resultsmentioning
confidence: 99%
“…Fairbairn et al (2016a) monitored 26 emerging contaminants including herbicides, pharmaceuticals and personal care products (PPCPs) in a mixed-use watershed in Minnesota over a 7-month period in 2012. Water samples were collected from wastewater treatment plant (WWTP) effluent, upstream and downstream sites on the Zumbro River.…”
Section: Steroid Hormonesmentioning
confidence: 99%
“…The mass balance determination of BPA during different WW treatment processes was carried out by Guerra et al They reported median removal efficiencies of up to 77 % for treatment processes and mentioned that the operational conditions that most influenced BPA removal are solids retention time (SRT), hydraulic retention time (HRT), and mixed liquor suspended solids (MLSS).They also reported that the sorption tendency of BPAs to WWS was strongly influenced by HRT and degree of nitrification. A mass balance analysis and a comparison of WW effluent and upstream sources on the fate of ECs in a mixed‐use watershed was conducted by Fairbairn et al They reported that the mass balances showed that effluent transport dominated ECs loading to the watershed and further suggested that upstream dominated ECs should be monitored during high‐flow events and seasons because increased concentrations that occur during these times will also represent the greatest loadings. Furthermore, Thiebault et al determined the removal efficiency of pharmaceuticals in WWTPs by considering fate assessment and mass balance assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Quantities of ECs are expressed relative to value observed in the influent (%). Data taken from elsewhere …”
Section: Introductionmentioning
confidence: 99%